Financial performance analysis of cigarette companies listed on the Indonesia stock exchange - Maria Roswita Takene; Stanis Man; Rere Paulina Bibiana (Institute of Computer Science (IOCS), 2023)
This study aims to determine the comparisons and factors that distinguish the financial performance of cigarette companies listed on the Indonesia Stock Exchange in 2018-2021. The method used in this research is a quantitative descriptive technique using financial ratio analysis. Meanwhile, to determine the weight of a good or bad assessment of a cigarette company's financial performance, it is determined by calculating financial ratios based on an analysis of financial statements according to cashmere in 2018, 2019 and Jumingan in 2014. The final results of the study show that: (1) PT. Gudang Garam Tbk. shows that the company's financial performance is in the unhealthy category. (2) PT. Hanjaya Mandala Sampoerna Tbk. shows that the company's financial performance is in the healthy category. (3) PT. Bentoel Internasional Investama Tbk. shows that the company's financial performance is in the unhealthy category. (4) PT. Wismilak Inti Makmur Tbk. shows that the company's financial performance is in the fairly healthy category. Based on the research results, it is suggested that companies can improve their existing performance, especially on the indicators Current Ratio, Quick Ratio, cash Ratio, DAR, DER, ROA, ROE, accounts receivable turnover, total assets, working capital